Antimicrobial stewardship program in COVID-19 era: Ruin of the reign? - Eatemadi, Arash; Golchinheydari, Sirous; Reesi, Mohammed Al; Maqbali, Majid Al; Maqbali, Talib Al Maqbali; Wahaibi, Aiman Al (Journal of Biomedical and Pharmaceutical Research, 2021)
COVID-19 is the most important matter in the medical field worldwide in 2020. Although COVID-19 is a viral disease, the threshold to antibiotic prescription for COVID-19 patients is low, partly because of WHO recommendations and previous experiences from influenza, despite the lack of strong evidence of co-infection or superimposed bacterial infection in COVID-19 patients. Antibiotic stewardship program (ASP) could play an important role in this period, otherwise, we will face a crisis of superbugs in the early future.Keywords:  COVID-19, Antibiotic stewardship program (ASP), Superbugs